DIGITAL TRANSFORMATION IN THAI PUBLIC HEALTH: A TAM ANALYSIS OF TECHNOLOGY ADOPTION - PIMPAPORN, Thittarat; SANGPERM, Nuanluk; PIMPAPORN, Werayut; JUNJAROENWONGSA, Daranee; HENGTRAKULVENICH, Nantawan (Asian Administration and Management Review, 2025)
This study explores factors influencing digital technology adoption in the Thai public health sector, using an extended Technology Acceptance Model (TAM 3). Data from 238 personnel at the Office of Disease Prevention and Control Region 6 were analyzed through multiple linear regression. The findings indicate that perceived usefulness is significantly influenced by image, output quality, and job relevance, while perceived ease of use is shaped by objective ability, computer self-efficacy, enjoyment, playfulness, and perception of external control. Furthermore, subjective norm impacts image, and both perceived usefulness and ease of use are critical for intention to use digital technology. The findings offer actionable insights for government agencies to enhance digital technology adoption. Understanding these factors enables the design of effective strategies to promote digital transformation in Thailand’s public health sector, supporting the goals of modernization, efficiency, and citizen-centric service delivery.